The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1088/0953-8984/20/31/315007
|View full text |Cite
|
Sign up to set email alerts
|

Capillary adhesion between elastic solids with randomly rough surfaces

Abstract: I study how the contact area and the work of adhesion, between two elastic solids with randomly rough surfaces, depend on the relative humidity. The surfaces are assumed to be hydrophilic, and capillary bridges form at the interface between the solids. For elastically hard solids with relative smooth surfaces, the area of real contact and therefore also the sliding friction, are maximal when there is just enough liquid to fill out the interfacial space between the solids, which typically occurs for dK ≈ 3hrms,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
104
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 46 publications
(96 reference statements)
5
104
0
Order By: Relevance
“…The effect of adhesion has only been determined for a limited range of parameters, and we hope that our predictions will be compared with future results from this model. Persson has also presented a theory of capillary adhesion (38) that includes a calculation of the distribution of surface separations and may be able to predict A att .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of adhesion has only been determined for a limited range of parameters, and we hope that our predictions will be compared with future results from this model. Persson has also presented a theory of capillary adhesion (38) that includes a calculation of the distribution of surface separations and may be able to predict A att .…”
Section: Discussionmentioning
confidence: 99%
“…This is due to a force in the capillary action which pulls the surfaces together [15,35]. However, this is not the case when one of the materials is soft.…”
Section: Capillary Adhesionmentioning
confidence: 99%
“…Persson [15] analysed this situation for a hard, rough surface (R q = 6 µm) contacting a smooth, elastically soft solid at a nominal applied pressure of 0.1 MPa, where the Poisson's ratio of the soft solid was 0.5 and the Young's modulus varied from 3 to 300 MPa. Persson [15] found that for elastically soft solids (not in this case skin, but Persson refers to a number of case studies involving biological systems in this work including tree frog feet), when the water level on the surface decreases, there is a large increase in the area of contact.…”
Section: Capillary Adhesionmentioning
confidence: 99%
See 1 more Smart Citation
“…As dimensions shrink into the nanoscale, capillary forces become increasingly important and can be the dominant source of adhesion between surfaces [11][12][13]. For example, they often prevent micro-or nanoelectromechanical systems from functioning under ambient conditions or lead to damage in their fabrication processes [14].…”
Section: Introductionmentioning
confidence: 99%